ANALISIS PEMBINGKAIAN DAN KONSTRUKSI REALITAS HIMBAUAN PELONGGARAN PENGGUNAAN MASKER OLEH PRESIDEN REPUBLIK INDONESIA JOKO WIDODO PADA TEMPO.CO - Krisna Danil Avivi Setiawan (2023)
This research examines the online news portal tempo.co in framing and constructing the reality of the event of the call for easing the use of masks by the President of the Republic of Indonesia Joko Widodo and producing it into news text. This research was conducted using qualitative methods and using the Robert N Entman framing analysis method by analyzing the news coverage by tempo.co about the call for easing the use of masks by the President of the Republic of Indonesia, Joko Widodo. The results of the study found that tempo.co framed it with critical framing and constructed the reality of the call for easing the use of masks by assessing that easing the use of masks could not be implemented.